2020
DOI: 10.3390/molecules25030520
|View full text |Cite
|
Sign up to set email alerts
|

Fast Isolation of Flavonoids from the Endemic Species Nolana ramosissima I.M. Johnst and Its Endothelium-Independent Relaxation Effect in Rat Aorta

Abstract: The infusion of the desertic plant Nolana ramosissima I.M. Johnst showed vascular smooth muscle relaxation in rat aorta and the presence of several phenolic compounds, which were detected by high resolution UHPLC-Orbitrap-HESI-MS. In addition, five flavonoids were rapidly isolated from a methanolic extract using high-performance counter-current chromatography (HPCCC). The N. ramosissima extract showed endothelium-independent relaxation effect in rat aorta. Sixty-one compounds were detected in the infusion, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The compound structures were assigned based on HRMS and 1D and 2D NMR ( Supplementary Figure S1 , Figure 1 ). The compound 5-hydroxy-7-methoxy flavanone (pinostrobin) has previously been reported in the literature ( Cifuentes et al, 2020 ) and 3,5-dimethoxystilbene, was isolated from several plants, including Alpinia katsumadai ( Ngo and Brown, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…The compound structures were assigned based on HRMS and 1D and 2D NMR ( Supplementary Figure S1 , Figure 1 ). The compound 5-hydroxy-7-methoxy flavanone (pinostrobin) has previously been reported in the literature ( Cifuentes et al, 2020 ) and 3,5-dimethoxystilbene, was isolated from several plants, including Alpinia katsumadai ( Ngo and Brown, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…When chemical structures of the compound 1 (pinostrobin; 5-hydroxy-7-methoxy-flavanone) and 3 (sakuranetin; 4′,5 -dihydroxy-7-methoxyflavanone) were compared, we discovered that the increase of the vascular relaxation of compound 3 might be due to the inclusion of the free OH group at position 4′. In a previous study, we found that free OH groups in position 5 and 3′ were also important for the increase of the vascular relaxation in isolated metabolites from N. ramosissima [ 36 ]. On the other hand, the vascular relaxation effect between compounds 3 and 4 was not significantly different ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, there are also no scientific reports concerning to the antioxidant and enzyme inhibition potential of extracts from the plant. Our group recently investigated the enzyme inhibitory properties plus the antioxidant and chemical fingerprinting of several Chilean native plants and fruits [8][9][10][11][12]. Following our studies on South American plants, we now report the phenolic fingerprinting from ethanolic extracts of Lloime leaves by UHPLC-MS analysis, antioxidant activity and enzyme inhibitory potential (against cholinesterase and tyrosinase) for the first time.…”
mentioning
confidence: 99%